2020
DOI: 10.1364/boe.410617
|View full text |Cite
|
Sign up to set email alerts
|

Artefact removal in ground truth deficient fluctuations-based nanoscopy images using deep learning

Abstract: Image denoising or artefact removal using deep learning is possible in the availability of supervised training dataset acquired in real experiments or synthesized using known noise models. Neither of the conditions can be fulfilled for nanoscopy (super-resolution optical microscopy) images that are generated from microscopy videos through statistical analysis techniques. Due to several physical constraints, a supervised dataset cannot be measured. Further, the non-linear spatio-temporal mixing of data and valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, the postprocessing algorithms can be designed to compensate for such artifacts. 34 Figure 1e shows the radial line-scan of ground-truth, widefield, and final super-resolved image of the fluorescent sample. From the radial line scan profile, it is observed that separations more than 250 nm are fairly resolved, which signifies that we achieve around 3-fold lateral resolution enhancement over the diffraction limit (750 nm) using the sinusoidal lattice illumination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the postprocessing algorithms can be designed to compensate for such artifacts. 34 Figure 1e shows the radial line-scan of ground-truth, widefield, and final super-resolved image of the fluorescent sample. From the radial line scan profile, it is observed that separations more than 250 nm are fairly resolved, which signifies that we achieve around 3-fold lateral resolution enhancement over the diffraction limit (750 nm) using the sinusoidal lattice illumination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The presence of such angle-specific artifacts indicates that this is primarily caused by the illumination rather than the reconstruction. However, the postprocessing algorithms can be designed to compensate for such artifacts Figure e shows the radial line-scan of ground-truth, widefield, and final super-resolved image of the fluorescent sample.…”
Section: Resultsmentioning
confidence: 99%
“…The wide-field resolution of chip-based TIRFM and the potential of super-resolution through both single molecule localization and fluctuations based techniques have already been investigated [7][8][9]. At the same time, resolution and reconstruction quality of MUSICAL have also been studied previously [10,11]. The scope of utilizing the chip-based illumination for super-resolution using MUSICAL is new and the focus of the current article.…”
Section: E Resolution Limit and Relationship With The Spatial Frequen...mentioning
confidence: 99%